Atmospheric Dry Hydrogen Plasma Reduction of Inkjet‐Printed Flexible Graphene Oxide Electrodes. Issue 5 (16th February 2018) - Homola, Tomáš; Pospíšil, Jan; Krumpolec, Richard; Souček, Pavel; Dzik, Petr; Weiter, Martin; Černák, Mirko
Abstract: This study concerns a low‐temperature method for dry hydrogen plasma reduction of inkjet‐printed flexible graphene oxide (GO) electrodes, an approach compatible with processes envisaged for the manufacture of flexible electronics. The processing of GO to reduced graphene oxide (rGO) was performed in 1–64 s, and sp 2 /sp 2 +sp 3 carbon concentration increased from approximately 20 % to 90 %. Since the plasma reduction was associated with an etching effect, the optimal reduction time occurred between 8 and 16 s. The surface showed good mechanical stability when deposited on polyethylene terephthalate flexible foils and significantly lower sheet resistance after plasma reduction. This method for dry plasma reduction could be important for large‐area hydrogenation and reduction of GO flexible surfaces, with present and potential applications in a wide variety of emerging technologies. Abstract : Prints charming : A low‐temperature method for dry hydrogen plasma reduction of inkjet‐printed flexible graphene oxide (GO) electrodes is presented. The enhanced electrical and chemical properties of GO ink are attributed to time‐efficient reduction and hydrogenation by atmospheric large‐area hydrogen surface plasma suitable for roll‐to‐roll manufacture.